Supervising in the Implementation of Integrated Pest Management (IPM) in good Horticultural Practices in the Sembalun agrotourism area - Sarjan, M.; Fauzi, Taufik; Thei, Ruth Stella; Nikmatullah, Aluh; Sarjan, Achmad Fajar NarotamaÂ (Pascasarjana Universitas Mataram, 2024)
The use of natural enemies as pest control has long been known, but has been largely replaced by the rapid development of chemical pesticide industry technology, especially since the green revolution. One alternative pest control technology that is quite promising to be developed is the use of biological agents (predators or parasotoids) that have more natural characteristics than chemical characteristics. With the presence of natural enemies which are then used to suppress pest populations, it will be safe for human health and the environment. It can be hoped that the agricultural products produced will be acceptable and highly competitive on the global market. Considering the Sembalun area as a tourism destination, it will be very relevant if the local community understands good horticultural practices. The intervention of using technology for farmers as an alternative in good Horticultural Cultivation is highly expected by farmers in the Sembalun area. Therefore, assistance is needed to implement integrated Pest Management in good Horticultural practices. The method used in this activity is the Action Research Method by applying a Participatory Action Program approach from participants through discussion and group work in all activities. The result is that farmers are very interested in implementing good horticultural cultivation, especially with habitat management approaches such as using refugia plants to control pests. Participating farmers increase their knowledge and skills to recognize differences in pests and natural enemies (predators and parasitoids) found on potato plants that are integrated with refugia plants. The target group has increased knowledge and understanding of the importance of implementing Integrated Pest Management (IPM) practices in horticultural cultivation. It is hoped that training and assistance activities for healthy horticultural cultivation efforts will continue both by the university team and related agencies. This kind of activity needs to be continued by the participating group and spread to other groups nearby. There is a need for assistance in applying for Prima 3 and Prima 2 food safety certification to farmer groups in the Sembalun Agrotourism Area, so that the number of products from certified horticultural business actors will increase. Activities to implement Integrated Pest Management in horticultural farming business groups in the Sembalun Tourism Area need to continue